The impacts of physical workplace environment (PWE) on employees productivity - Abdul Hamed, Sapiah; Mohd. Hussain, Mohd. Ramzi; Md Jani, Haza Hanurhaza; Sabri, Syikh Sazlin Shah; Rusli, Nazrul (Asian Scholars Network (002903215-H), 2023)
The paper reviews the impacts of the physical workplace environment (PWE) on employees' productivity, focusing on the pivotal role of the physical environment and its implications for employee well-being. The study emphasises that the physical environment is a critical factor influencing the activities of employees concerning global issues, thereby impacting productivity, efficiency, satisfaction, and absenteeism. The paper employs analytical reviews of the related articles to justify the impact of the physical workplace environment (PWE) on employees' productivity. The content analysis is used to analyse the literature framework of the article. The findings revealed the significance of the physical environment within the workplace, elucidating itsprofound influence on employee well-being, productivity, and satisfaction. The findings highlight the substantial role of employers in shaping the physical workplace environment and its reflecting impact on employee focus and productivity. A well-designed, comfortable, and conducive workplace has a positive influence on employee satisfaction, recognising employees as a vital asset in achieving organisational success. Consequently, creating an excellent physical workplace environment can significantly enhance employee productivity, encouraging employers to prioritise and provide such an environment, thus contributing to sustainable environmental health and fostering safe workplace practices.